Hospital mismanagement an investigative study on the violations and the viability of the hospital detention law - Decena, Karlitos Brian Uy (2012)
"This thesis investigates the violations on the Republic Act 9439 or the Hospital Detention Law and examines its effects on the patients and hospitals since its passage in 2007. Using theories such as Legal Realism, Convergence Theory and Network Theory and Analysis in Organizations as the basis of its framework, the study analyzes the different perceptions of the health stakeholders regarding the law, resulting in its weak implementation. The researchers employed qualitative methods such as purposive sampling, people and paper trails and review of secondary data. In a third world country were national budgets are often scarce, the law is clearly a manifestation on the lack of support the health sector receives from the state. Experts say that hospital detentions would not exist only if the government regards health as one of its priorities. The findings of this study are journalistically written in a three-part investigative report."